Numerical modeling and design of precast prestressed UHPFRC I beams - Gidrão,Gustavo de Miranda Saleme (2021)
ABSTRACT: Ultra-high-performance fiber reinforced concrete (UHPFRC) is a new material developed to present superior properties, as high compressive strength (higher than 130 MPa), high durability, and satisfactory ductile behavior. This paper reports the procedure to design precast UHPFRC beams, subject to flexural loads. First, an I-girder AASHTO Type II was designed, and simulated. Next, I-beams with diverse depths and steel ratios were designed, and simulated considering a four-point bending load test. It was found that the classical design equations used to predict the strength bending moment (Mrd) showed good accuracy with the simulated models with a 4.5% error.